Implementation of the FIFO System in the Management of Raw Material Inventory in the Kitchen at R-Gina Hotel Pemalang - Alamsyah, Sandi; Putri, Julian Andriani (PT. Banjarese Pacific Indonesia, 2024)
This research aims to analyze the implementation of the First In First Out (FIFO) system in managing raw material inventory in the kitchen of Hotel R-GINA Pemalang. The research method used is qualitative, focusing on direct observation, in-depth interviews, and document analysis related to the inventory management process. Although the FIFO system has been widely studied in the context of manufacturing and supply chains in general, this research provides new insights into its application in a hotel kitchen operational environment. The research results show that the implementation of the FIFO system in the kitchen of Hotel R-GINA Pemalang has helped improve the efficiency of raw material usage and reduce the risk of spoilage or expiration. However, several challenges were found in its implementation, such as limited storage space and the need for staff training. The conclusion of this research emphasizes the importance of the FIFO system in raw material inventory management in the hospitality industry. The proposed recommendations include improving storage infrastructure, developing a digital recording system, and ongoing training programs for kitchen staff.